Comparison of Intracranial Aneurysms Treated by 2-D Versus 3-D Coils: A Matched-Pairs Analysis - Lang, Stefan; Rösch, Julie; Gölitz, Philipp; Kloska, Stephan; Struffert, Tobias; Dörfler, Arnd (Clinical Neuroradiology, 2017)
OBJECTIVE: Knowledge on the influence of 2D and 3D coils to occlude intracranial aneurysms is poor. Therefore, aim of our analysis was to evaluate whether the use of 3-D versus 2-D coils alone may improve the efficacy of endovascular aneurysm treatment. PATIENTS AND METHODS: We performed a matched pair analysis comparing aneurysms treated by 3-D coils as initial "framing" coils to aneurysms treated exclusively by 2-D coils. Number of coils, implanted coil length/volume, and associated packing density were calculated. Aneurysmal occlusion was assessed and monitored 6 months (DSA; magnetic resonance angiography (MRA)) and 18 months (MRA) after embolization. Periprocedural complications and retreatment rate of each group were analyzed. RESULTS: Our retrospective analysis revealed 50 pairs. Concerning the 3-D group, number of coils (353 in total, median 7; p = 0.002), implanted coil length (55.69 ± 48.4 cm), implanted coil length per volume (5.92 mm/mm3), and packing density (30 %; p = 0.017) was higher than in the 2-D group (259 in total, median 5 coils; 38.52 ± 43.13 cm; 4.54 mm/mm3; 23 %). Occlusion was not significantly different immediately after treatment but at 6 and 18 months follow-up in favor of 3-D coils. Retreatment was performed in 2 cases of the 3-D group and in 3 cases of the 2-D group and therefore in a similar range (p = 0.564). CONCLUSION: Initial use of 3-D coils revealed a higher packing density and a higher long-term occlusion. Therefore, we recommend initial use of 3-D coils.
EVALuna2:33475